2021
DOI: 10.3390/app11041720
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Hydration Process in Carbon Nanotube Reinforced Cement-Based Composites Using Nonlinear Elastic Waves

Abstract: There is currently an increased need for associating construction material properties and behavior with the nature of their microstructure. One of the major issues in this context is the need for understanding the curing process in freshly poured cement-based materials. This is particularly important when nanoreinforcement materials, such as carbon nanotubes, are used to enhance the mechanical behavior and multifunctionality of the final structure. The solidification point, at which the state of liquid suspens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Meanwhile, the values of UCS for the D-3 sample (30% CP) and group E samples (40% CP) show a slight increase. Previous investigations have shown that the strength of the CGFB samples is mainly determined by the cement hydration [30][31][32][33][34]. Generally, the stronger the cement hydration is, the larger the corresponding strength of the CGFB sample is.…”
Section: Uniaxial Compression Test Resultsmentioning
confidence: 99%
“…Meanwhile, the values of UCS for the D-3 sample (30% CP) and group E samples (40% CP) show a slight increase. Previous investigations have shown that the strength of the CGFB samples is mainly determined by the cement hydration [30][31][32][33][34]. Generally, the stronger the cement hydration is, the larger the corresponding strength of the CGFB sample is.…”
Section: Uniaxial Compression Test Resultsmentioning
confidence: 99%